An isothermal titration calorimetry method for monitoring the removal of ethylenediamine tetra-acetic acid from apo-proteins - Ying Ge; Wen-Ming Wang; Tingjun Liu (Results in Chemistry)
Superbug infection caused by New Delhi metallo-β-lactamase (NDM-1) has grown into an emerging threat. EDTA is one of the most commonly used Zn(II) clelators for preparation of apo-metallo-β-lactamases (apo-MβLs) and further Co(II)-substituted MβLs for spectroscopic characterization of the enzymes. However, the removal of EDTA from the apo-proteins is rarely verified. Here, we provide a convenient and quick isothermal titration calorimetry (ITC) method for real-time monitoring of the removal of EDTA from apo-NDM-1. This ITC method can be used for monitoring the removal of clelators from apo-MβLs, even wide apo-matalloproteins, which enable one to prepare Co(II)-substituted proteins for further structural and mechanistic studies.